Case report: A case of perinodal atrial tachycardia and review of the relevant clinical anatomy surrounding the retroaortic node - Raina, Anvi; Tan, Nicholas Y.; Fatunde, Olubadewa A.; Asirvatham, Samuel J.; DeSimone, Christopher V. (Frontiers in Cardiovascular Medicine, 2023)
A 70-year-old female presented with incessant supraventricular tachycardia that was refractory to metoprolol succinate and sotalol. ECG revealed a narrow complex tachycardia with a rate of 163 beats per minute with a short RP relationship. She had salvos of atrial tachycardia which led to a severe reduction in ejection fraction as noted on echocardiography and hemodynamic instability. An electrophysiological study was performed, and findings suggested this to be an atrial tachycardia with earliest activation were perinodal. on the atrial septum. Radiofrequency ablation was carried out along the septum and associated structures to surround this region including the right atrium, non-coronary sinus of Valsalva, and the left atrium (anterior wall outside of the right superior pulmonary vein) to isolate this area and surround the focus with ablation lesions. The patient has down well and was started on flecainide post-procedure and continues to do well without any recurrence on low-dose flecainide at 8 months.